Three coordination polymers as a multi-responsive luminescent probe for the detection of Fe3+, Cr2O72− and antibiotic in aqueous media. (15th January 2022) - Ding, Ji; Li, Ning; Sun, Dan-Lin; Zhu, Yue; Cheng, Wei-Wei; Chen, Xuan-Rong; Xue, Yun-Shan
Graphical abstract: Three Co(II)/Zn(II) CPs have been synthesized under solvothermal conditions and complex 2 can act as multi-responsive luminescent probe to detect the Fe 3+ cation, Cr2 O7 2− anion and nitrofuran antibiotic (NZF) in aqueous media with high sensitivity, selectivity and low detection limits. Abstract: Three coordination polymers (CPs), namely {[Co(L)(dpa)]·H2 O}n (1 ), {[Zn(L)2 (dpb)]}n (2 ) and {[Zn(L)(dpe)]}n (3 ), have been assembled through a dual-ligand strategy of a semi-rigid dicarboxylic acid (H2 L = 1, 4-bis(4-phenoxy)benzenedicarboxylic acid) with the help of different N -donor co-ligands (dpa = di(pyridin-4-yl)amine, dpb = 1, 4-di(pyridin-4-yl)benzene), dpe =  trans -1, 2-di(4-pyridyl)ethylene). Single crystal X-ray diffraction analyses reveals that compound 1 is a 4-fold interpenetrating 2D sql network and compound 2 is a 2-fold interpenetrating 2D sql network, although the final structures are different because of various inter-layer stacking modes. Compound 3 is a 8-fold interpenetrating 3D dia framework containing an octahedral cage. A photoluminescence investigation shows that compounds 2 and 3 exhibit strong fluorescence originating from the intra-ligand charge transfer transitions. Benefiting from its chemical stability and luminescent properties, compound 2 possesses multi-functional fluorescent responses toward the Fe 3+ ion, the Cr2 O7 2− ion and the NZF antibiotic in aqueous medium. The K SV values of compound 2 are 4.68 × 10 4 M −1 for the Fe 3+ ion, 7.23 × 10 4 M −1 for the Cr2 O7 2− anion, and 1.03 × 10 4 M −1 for the NZF antibiotic. Additionally, the possible mechanism for the luminescence quenching has been investigated.